2018
DOI: 10.14419/ijet.v7i3.15.17407
|View full text |Cite
|
Sign up to set email alerts
|

Mind mapping Approach in Learning History

Abstract: Currently, most Malaysian teenagers know very little about Islamic history and its civilizations.  Although Islamic history and civilizations are covered briefly in Malaysian school syllabus, appreciation towards the subject is very little.  This is because of traditional approach of learning Islamic history does not appealing enough for the students to enjoy and understand the subject matter.  The capability of new powerful multimedia tools have enable an improved applications to be developed in order to faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…01). Experiments conducted by scientists as part of studying the possibilities and effectiveness of mind maps showed that even students who did not succeed in the program felt their involvement in the topic under study due to the fact that they had a holistic picture of events supported by their own associations (Dhiyauddin, 2018).…”
Section: Research Questionsmentioning
confidence: 99%
“…01). Experiments conducted by scientists as part of studying the possibilities and effectiveness of mind maps showed that even students who did not succeed in the program felt their involvement in the topic under study due to the fact that they had a holistic picture of events supported by their own associations (Dhiyauddin, 2018).…”
Section: Research Questionsmentioning
confidence: 99%
“…Other scholars apply mind map in different subjects of Physics ( (Li, Tran, & Le, 2016), Geography (Nguyen & Pham, 2018;Sari, Sumarmi, Utomo, & Astina, 2019), Language (Tran, 2020). Dhiyauddin, Ahmad, Ismail, & Diah (2018) argue that history is a boring subject and students always avoid from learning it. That applying some software such as Adobe Photoshop, Adobe Illustrator and Unity is useful to create mind map; and that using diversified colors and pictures, shapes has high meaning in teaching and learning history, in which including Islamic history.…”
Section: Introductionmentioning
confidence: 99%